2022
DOI: 10.1371/journal.pone.0269300
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of in vivo stretching regimens on inflammation and its relevance to translational yoga research

Abstract: Objective To conduct a systematic review evaluating the impact of stretching on inflammation and its resolution using in vivo rodent models. Findings are evaluated for their potential to inform the design of clinical yoga studies to assess the impact of yogic stretching on inflammation and health. Methods Studies were identified using four databases. Eligible publications included English original peer-reviewed articles between 1900–May 2020. Studies included those investigating the effect of different stret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 89 publications
0
8
0
Order By: Relevance
“…The recent results in medical and sports scientific literature indicate that chronic SS exercises have the potential to improve muscle strength and power [5,20]. Further investigations could examine the benefits of chronic SS exercises in old, healthy, and ill individuals, as compared to young, active, and well-trained persons, as well as compared to professional athletes [20,30,[63][64][65][66][67].…”
Section: Biomechanical and Biological (Cellular And Molecular) Mechan...mentioning
confidence: 99%
“…The recent results in medical and sports scientific literature indicate that chronic SS exercises have the potential to improve muscle strength and power [5,20]. Further investigations could examine the benefits of chronic SS exercises in old, healthy, and ill individuals, as compared to young, active, and well-trained persons, as well as compared to professional athletes [20,30,[63][64][65][66][67].…”
Section: Biomechanical and Biological (Cellular And Molecular) Mechan...mentioning
confidence: 99%
“…to positively impact inflammation (Muñoz-Vergara, Grabowska, et al, 2022). In clinical studies, yoga has been shown to reduce stressrelated cellular aging, increase telomerase activity, and preserve telomere length (Krishna et al, 2015;Lavretsky et al, 2013).…”
Section: Ta B L E 2 (Continued)mentioning
confidence: 99%
“…Yoga may impact cellular and molecular hallmarks of aging. In rodents, stretching protocols similar to yogic stretching seemed to positively impact inflammation (Muñoz‐Vergara, Grabowska, et al, 2022 ). In clinical studies, yoga has been shown to reduce stress‐related cellular aging, increase telomerase activity, and preserve telomere length (Krishna et al, 2015 ; Lavretsky et al, 2013 ).…”
Section: Mind–body Therapies Are Promising Approaches To Frailty Prev...mentioning
confidence: 99%
“…Yoga as therapeutic science received increasing attention over the past decades and has been an object of study with a high number of scientific publications in different medical disciplines, demonstrating great therapeutic effects and benefits for both physical and mental/cognitive health. A large number of clinical studies on Yoga as a medical approach for different pathologies science have been published in highly rated/top-scored journals in various medical fields, specifically in cardiology for cardiovascular diseases [ 24 , 25 , 26 ], coronary heart disease [ 27 ], hypertension [ 28 ], atrial fibrillation and arrhythmia [ 29 ] and vasovagal syncope [ 30 ]; in internal medicine for metabolic syndrome [ 31 , 32 ], irritable bowel [ 33 ], inflammatory markers [ 34 , 35 ] and immune system [ 36 ]; in neurology/psychology for stress, anxiety and burnout [ 37 , 38 ]; in pneumology [ 39 , 40 ]; in orthopedics/physiatry for chronic pain and pain-associated disorders [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ] and disc herniation [ 45 , 46 , 47 ]; in occupational and preventive medicine and public health [ 37 , 48 ].…”
Section: Introductionmentioning
confidence: 99%